Paciente de sexo Femenino de 62 años de edad con Diabetes mellitus tipo II. - Troya Altamirano, Lissette Alexandra (2020)
This clinical case is of an adult female patient of 62 years of age,Ecuadorian with medical diagnosis of Diabetes mellitus type II, who goes to the consultation for presenting signs and symptoms of blurred vision, fatigue, increased fluid intake and frequent urination with 4 weeks of evolution, the patient refers to a family pathological history, mother deceased from acute myocardial infarction, but it does not refer to personal surgical history or toxic habits, he also referred not to consume any type of drug, in his physical examination presents a weight of 75 kg, size 175 cm, waist circumference of 92 cm and a hip circumference of 100 cm, in addition to performing low physical activity (sedentary), temperature: 37oC and a heart rate 80 beats per minute , rum corresponding biochemical examinations are performed and their results were: Fasting Glycemias 325 mg/dl, Hemoglobin Glycosylated 10.5%, Total Cholesterol 130 mg/dL, Triglycerides 118 mg/dL, HDL 41 mg/dL, LDL 70 mg/dL, Creatinine 0.9 mg/dL. In this clinical case a dietary treatment will be performed - appropriate and optimal therapeutic to improve its metabolic state, in addition to providing with an educational plan in order to avoid future complications and achieve beneficial long-term effects. In order to improve in the patient its metabolic status and consequently its nutritional status and quality of life; it proceeds in this way to provide informed knowledge of its therapeutic dietary treatment and once accepted the same; nutritional assessment is carried out by anthropometric indicators (body composition), biochemical assessment, presence of signs, symptoms and dietary assessment through food anamnesis. Subsequently, an educational dietary nutritional plan was carried out according to their needs focusing on permitted, not allowed foods and recommendations of the daily living that will allow him to understand the importance of following a controlled diet so that in this way he can maintain a favorable state of health and prevent complications related to this pathology, finally proceeded to carry out the monitoring of control per month to show the effects of the proposed nutritional intervention, where significant changes could be evident in the patient.